If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -100 + -6x = -12x + 56 Reorder the terms: -100 + -6x = 56 + -12x Solving -100 + -6x = 56 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -100 + -6x + 12x = 56 + -12x + 12x Combine like terms: -6x + 12x = 6x -100 + 6x = 56 + -12x + 12x Combine like terms: -12x + 12x = 0 -100 + 6x = 56 + 0 -100 + 6x = 56 Add '100' to each side of the equation. -100 + 100 + 6x = 56 + 100 Combine like terms: -100 + 100 = 0 0 + 6x = 56 + 100 6x = 56 + 100 Combine like terms: 56 + 100 = 156 6x = 156 Divide each side by '6'. x = 26 Simplifying x = 26
| y=0.50+30 | | (10-3.2n)n=2 | | 140=(n+94) | | 2-x+5+3x=13 | | -2(3h-2)-4h=-16 | | (2-d)-(2d-10)-(-4d)=50 | | 2(3x-5)=3(2x-4) | | SiNx+6+4x=114 | | 4x+2(X+10)=30+6x-10 | | 3x-10+5x=-74 | | -47-4k=5(2+3k) | | (8x^8)-(x^5)=0 | | -2(-3x-3)=-24 | | 29w-2w+8=4w+38 | | 6x+20-2x=60 | | 74=-x-7x-6 | | 83-23= | | -2=-4(-7y+1)+5(8+2) | | 4x-2(x+1)=26 | | 4.25(-2x+4)-8.25x=16.5-13.25 | | 15+10-5= | | -38+8n=-6+8(n-4) | | 10u+10u+5u= | | -2x-8+x=-8 | | 2(x+4)-4x=10 | | 18x^3+54x^2+40x=104 | | 4(a+-1)-5=3a+7 | | (7k)2= | | 11(2v+3)=-2v-8 | | 6b+7-4=14 | | 412*272= | | -4k+3(2k-5)=31 |